INOVASI PENDAMPINGAN PEMBERIAN ASI PADA IBU PASCASALIN MENINGKATKAN PENGETAHUAN, SIKAP DAN PERILAKU IBU MENYUSUI - Deswani Deswani; Yuli Mulyanti (Poltekkes Kemenkes Jakarta III, 2017)
Mentoring Innovations can be counseling to improve knowledge, attitude and behavior of the mother in giving BREAST MILK to the baby on the mother under labor. The purpose of the research was to identify the influence of breast feeding on mentoring Innovatio ns mother amid labor against the success of the knowledge, attitude and behavior of the mother in the exclusive breast feeding. Design research is quasi experiment with pre-and post test of nonequivalent control group design. Sampling techniques with accidental sampling consisting of 38 respondents to the intervention group and the control group respondents 30, analysis by using different test and analysis of multivariate regression with bivariat and linear. The results showed that respondents who received the intervention, the results showed that respondents who received the intervention, there is an increase in the score of knowledge amounted to2.514 with value t = 6.970, an increase in score value 2.353 attitude t = 13.179, and an increase in the score by 1.324 skills value t = 8.043. The most dominant factor influencing the behavior of mothers in breastfeeding is support the husband. It was concluded that there was significant influence innovation program intervention mentoring mom breast feedin g post childbirth on p-value of 0.000 to increased score of knowledge, attitudes and skills of respondents.